Enterprise Semantics : Aligning Service-Oriented Architecture with the Business bringing agility, transparency and integration to your web services infrastructure. - Fox, Joshua
Service oriented architectures (SOAs) are a significant step forward in aligning information technology with business goals. But SOAs are insufficient when the Web services of which they are typically composed use inconsistent terminologies and present different understandings of the real world environment that they are meant to support. Enterprises need transparency, a clear view of what is happening in the organization. They also need agility, which is the ability to respond quickly to changes in the internal and external environments. Finally, organizations require integration : the smooth interoperation of applications across organizationl boundaries. Encoding business concepts in a formal semantic model helps to achieve these goals and also results in additional corollary benefits. This semantic model serves as a focal point and enables automated discovery and transformation services in an organization.